3D Printing in analytical sample preparation. Issue 9 (16th March 2020) - Li, Feng; Ceballos, Melisa Rodas; Balavandy, Sepideh Keshan; Fan, Jingxi; Khataei, Mohammad Mahdi; Yamini, Yadollah; Maya, Fernando
Abstract: In the last 5 years, additive manufacturing (three‐dimensional printing) has emerged as a highly valuable technology to advance the field of analytical sample preparation. Three‐dimensional printing enabled the cost‐effective and rapid fabrication of devices for sample preparation, especially in flow‐based mode, opening new possibilities for the development of automated analytical methods. Recent advances involve membrane‐based three‐dimensional printed separation devices fabricated by print‐pause‐print and multi‐material three‐dimensional printing, or improved three‐dimensional printed holders for solid‐phase extraction containing sorbent bead packings, extraction disks, fibers, and magnetic particles. Other recent developments rely on the direct three‐dimensional printing of extraction sorbents, the functionalization of commercial three‐dimensional printable resins, or the coating of three‐dimensional printed devices with functional micro/nanomaterials. In addition, improved devices for liquid–liquid extraction such as extraction chambers, or phase separators are opening new possibilities for analytical method development combined with high‐performance liquid chromatography. The present review outlines the current state‐of‐the‐art of three‐dimensional printing in analytical sample preparation.